Вплив діджиталізації та дистанційних комунікацій на стратегію маркетинг-міксу освітніх послуг - Ткачук (Стахурська), Світлана Валеріївна; Стахурська, Світлана Антонівна; Стахурський, Валерій Олександрович (My University, 2021)
У статті розглядаються перспективи діджиталізації освіти, зокрема в аспекті формування стратегії комплексу маркетингу освітніх послуг. Аналізується вплив впровадження дистанційних технологій у поєднанні із онлайн-навчанням на елементи маркетинг-міксу освітньої послуги. Комплекс маркетингу пропонується розглядати як сукупність восьми взаємопов’язаних елементів, притаманних сервісній сфері: продукт, ціна, просування, розповсюдження, матеріальне середовище, фізичний доказ, процес та персонал. Встановлено, що найбільшого впливу від діджиталізації освіти зазнає матеріальне середовище освітнього сервісу, яке практично повністю трансформується у віртуальне середовище. Значною мірою матимуть місце зміни й щодо організації освітнього процесу. Так само відчує зміни контактний персонал освітньої послуги: перехід онлайн вимагатиме від викладачів розвитку нових soft skills та hard skills, бажання до прийняття змін. Діджиталізацію в освіті пропонується розглядати як перспективний напрям, який виведе освітній сервіс на новий рівень, надасть переваги як закладам освіти, так і здобувачам. Для успішної діджиталізації потрібно подолати ряд проблем, зокрема,проблеми з Інтернет-трафіком. The article considers the prospects of digitalization of education, in particular in terms of forming a strategy for the marketing of educational services. The influence of the introduction of distance technologies in combination with online learning on the elements of the marketing mix of the educational service is analyzed. The marketing complex is proposed to be considered as a set of eight interconnected elements inherent in the service sector: product, price, promotion, distribution, material environment, physical evidence, process and personnel. It is established that the greatest impact of digitalization of education is the material environment of educational services, which is almost completely transformed into a virtual environment: material facilities and equipment will be replaced by platforms for video conferencing and distance learning platforms, which will reduce the cost of educational services and will enable educational institutions to finance funds for development, in particular, the part of the environment that should remain material (laboratories for training medical students, pharmacists, training facilities for actors, etc.). There will be significant changes in the organization of the educational process, in particular, the problems of organizing this process in space will disappear, learning will involve a combination of online communications and the use of distance learning platforms, there will be multichannel communication with teachers, geographical barriers will disappear, including in the organization of meetings with professional specialists and stakeholders, the level of comfort will increase due to the integration of learning in the home space. The contact staff of the educational service will also feel the changes: the transition online will require teachers to develop new soft skills and hard skills, the desire to accept change. Digitalization in education is proposed to be considered as a promising area that will bring the educational service to a new level, will provide benefits to both educational institutions and applicants. Successful digitalization requires overcoming a number of problems, including problems with Internet traffic and resistance to change, but these problems can and must be overcome.
Keywords: маркетинг освітніх послуг; маркетинг-мікс освітніх послуг; дистанційне навчання; онлайн-навчання; діджиталізація освіти; віртуальне середовище освітніх послуг; дистанційні комунікації; онлайн комунікації; зміни в освіті; marketing of educational services; marketing mix of educational services; distance learning; online learning; digitalization of education; virtual environment of educational services; distance communications; online communications; changes in education; кафедра маркетингу; кафедра економіки праці та менеджменту